Assistance in Increasing the Efficiency of the Cost of Goods Sold for Herbal Medicine - Riris Zahrotul Fauziah; Rizki Dwi Farotul Khasanah; Hanif Rani Iswari (Trescode Green Organization, 2024)
The Community Service Program (PKM) aims to increase production efficiency and cost management in traditional herbal medicine businesses. Through a series of training and mentoring, this program focuses on implementing more effective and efficient cost management strategies, with the hope of increasing the competitiveness of herbal medicine products in the market. A qualitative approach was used to understand the obstacles and challenges faced by herbal medicine entrepreneurs in managing production costs. Qualitative data was collected through in-depth interviews with herbal medicine entrepreneurs and direct observation of the production process. Meanwhile, a quantitative approach is used to measure cost efficiency before and after the intervention. Quantitative data is collected through financial document analysis and surveys. The results of this program show a significant increase in production cost efficiency and participants' understanding of business financial management. The conclusion of this activity indicates that by implementing the right strategy, traditional herbal medicine businesses can further develop and compete in a wider market. Recommendations in the long term, product diversification and wider market penetration can be strategies to increase business sustainability. With a commitment to increasing efficiency and innovation, Satrio Turonggo Jati can continue to develop and make a positive contribution to the local and national economy.